Gastric aspirate cytology as a screening tool for neonatal sepsis: a prospective study from a tertiary care centre - Kumar, Ranjith; Reddy, Bhaskar; Soren, Chapay; Reddy, Venkataramana; ., Raheemunisa (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal sepsis is a clinical syndrome of bacteremia characterized by systemic signs and symptoms of infection in the first 28 days of life. It is responsible for 30-50% of the total neonatal deaths each year in developing countries. Gastric aspirate cytology has been used for neonatal infection. The presence of more than five polymorphs per high power field co-relate with neonatal infection. The objective of the present study was to evaluate the utility of gastric aspirate cytology as a screening tool for neonatal sepsis and to determine the polymorphonuclear leukocytes count in smear of gastric aspirate and correlating it with culture proven sepsis. Methods: This prospective observational study was conducted from February 2017 to January 2018 at level III Neonatal intensive care Unit of Sri Venkata Sai Medical College and Hospital, Mahabubnagar, Telangana. A total of 108 neonates with risk factor and / or clinical features of sepsis were included in the study. Results: Out of 108 neonates, 40 were blood culture positive and 68 were culture negative. Gastric aspirate smear showed ≥5 polymorphs in 30 and <5 polymorphs in 10 neonates with positive blood culture. Among blood culture negative cases, 20 had ≥5 polymorphs and 48 had <5 polymorphs in gastric aspirate smear. Gastric aspirate culture was positive in 48 neonates and negative in 60 neonates. Of the 48 gastric aspirate positive neonates, 45 had ≥5 polymorphs and 3 had <5 polymorphs in gastric aspirate smear. Similarly, among 60 gastric aspirate culture negative neonates, 55 had ≥5 polymorphs and 3 had <5 polymorphs in gastric aspirate smear. This was statistically significant (P<0.000001). Of 48 neonates with positive gastric aspirate culture, 30 had positive blood culture and 18 had negative blood culture. Conclusions: Gastric aspirate cytology is a good screening tool for neonatal sepsis added to a detailed perinatal history and clinical examination but does not completely substitute the present day available screening parameters.